The plantaris muscle – Anatomical curiosity or a structure with important clinical value? – A comprehensive review of the current literature - Gonera, B.; Kurtys, K.; Paulsen, Friedrich; Polguj, Michał; LaPrade, Robert F.; Grzelecki, Dariusz; Karauda, Piotr; Olewnik, Łukasz (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Purpose: Although the plantaris muscle is vestigial in humans, it is far too important to remain omitted. The aim of this study is to provide a comprehensive review of the existing literature focused on plantaris muscle clinical value, grafting usefulness and its morphological variations. Hopefully this study will be of great use for every medical practitioner due to its clarity and conciseness despite such broaden scope of this article. Material and Methods: The article is written based on 100 studies published since 1868 until 2020. During careful selection process 12 papers were dismissed due to their insufficient sample size, wrong methods used or results that were previously discovered. Results: Many aspects concerning the plantaris muscle are already well examined, summarized and described. However this study has shown how much we still do not know and which fields require further investigations. Conclusion: The anatomical variations of plantaris muscle morphology may cause mid-portion Achilles tendinopathy, tennis leg syndrome or increase the risk of failure while harvesting the tendons.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Achilles mid-portion tendinopathy; Autologous graft; Plantaris muscle; Popliteal region; Tennis leg